Task shifting in Mozambique: cross-sectional evaluation of non-physician clinicians' performance in HIV/AIDS care - Manuel Rolanda; Bastos Rui; Bacon Oliver; Martínez Martínez Pilar; Vallejo Torres José; Ghee Annette E; Mudender Florindo; Assan Américo; Brentlinger Paula E; Ramirez Li Lucy; McKinney Catherine; Nelson Lisa J (BMC, 2010)
Abstract Background Many resource-constrained countries now train non-physician clinicians in HIV/AIDS care, a strategy known as 'task-shifting.' There is as yet no evidence-based international standard for training these cadres. In 2007, the Mozambican Ministry of Health (MOH) conducted a nationwide evaluation of the quality of care delivered by non-physician clinicians (técnicos de medicina, or TMs), after a two-week in-service training course emphasizing antiretroviral therapy (ART). Methods Forty-four randomly selected TMs were directly observed by expert clinicians as they cared for HIV-infected patients in their usual worksites. Observed clinical performance was compared to national norms as taught in the course. Results In 127 directly observed patient encounters, TMs assigned the correct WHO clinical stage in 37.6%, and correctly managed co-trimoxazole prophylaxis in 71.6% and ART in 75.5% (adjusted estimates). Correct management of all 5 main aspects of patient care (staging, co-trimoxazole, ART, opportunistic infections, and adverse drug reactions) was observed in 10.6% of encounters. The observed clinical errors were heterogeneous. Common errors included assignment of clinical stage before completing the relevant patient evaluation, and initiation or continuation of co-trimoxazole or ART without indications or when contraindicated. Conclusions In Mozambique, the in-service ART training was suspended. MOH subsequently revised the TMs' scope of work in HIV/AIDS care, defined new clinical guidelines, and initiated a nationwide re-training and clinical mentoring program for these health professionals. Further research is required to define clinically effective methods of health-worker training to support HIV/AIDS care in Mozambique and similarly resource-constrained environments.